Tobacco advertising on mini-motors - Darling, H; Reeder, A I (Tobacco control, 2006)
Even in a country with legislation that explicitly removes tobacco brand images and advertising there remains a need to be vigilant for tobacco product promotion, whether this promotion is directly as a result of tobacco manufacturer activity or not.